Petrographic Study of Some Paleoproterozoic Sedimentary Rocks in the Chagupana and Tarkwa Areas of Ghana - Brako, Blestmond A; Foli, Gordon; Amedjoe, Chiri; Gawu, Simon K.Y (International Journal of Geography and Geology, 2020)
This study geologically compares conglomerate and sandstone units in the Chagupana area of the Upper West Region and the Kawere conglomerate and Kawere-Huni-Banket sandstone units in the Tarkwa area of the Western Region in Ghana. Some work in the area has over time proposed that rocks from the two areas as similar based on only field relations, hence the need for more detailed work for re-classification. Macro and microscopic studies of the composition, mineralogy and texture of the rock types reveal that the conglomerates in both areas are metamorphic-clast units, greenish-grey, polymictic, foliated and texturally immature. Compositionally and mineralogically, Chagupana conglomerate is matrix-supported and immature, while Kawere conglomerate is clast-supported and mature; these constraint similarities between the conglomerates to only composition. The sandstones from both areas have similar mineralogical compositions, but with decreasing feldspar in the order of Chagupana>Huni>Kawere>Banket. Texturally, all the sandstones are sub-mature, well-indurated and angular-rounded; except the Huni sandstone, which is fine to medium-grained, while the other sandstones are medium-coarse-grained. Based on the feldspar contents, the Chagupana, Huni, Banket and Kawere sandstones classify as greywacke, feldspathic arenite, sub-litharenite and sub-feldspathic-feldspathic arenite, respectively. The greywacke and sandstones have the same cementing materials as quartz, sericite and chlorite. Concluding, the Chagupana rocks are not entirely the same as those from the Tarkwaian Group, probably due to differences in provenance.